Understanding parents’ experiences of disease course and influencing factors: a 3-year follow-up qualitative study among parents of children with functional abdominal pain - Mette Brekke; Anne Brodwall (BMJ Open)
Objective Functional abdominal pain is a common symptom in children and adolescents. Three years ago, we investigated the experiences among parents whose children had chronic abdominal pain but no somatic diagnosis. The aim of the present follow-up study was to explore those families’ current situations.Design Interviews with open questions about the families’ current pain situations were carried out by the first author. Interviews were audio-recorded and transcribed, and subsequently analysed using descriptive content analysis.Setting Urban and rural areas in two municipalities in Southern Norway.Participants Parents of children with abdominal pain who had been referred to a local hospital by their general practitioner and had been discharged without a somatic diagnosis. Fifteen parents of 14 children aged 8–17 years who had also been interviewed in 2016.Results Nine of the children had recovered from their abdominal pain. During the pain period, the parents reported frustration with not having a diagnosis nor a specific treatment for their child’s abdominal pain. The siblings in some families received less attention and were afraid that something serious might happen to their sister or brother. The parents wished that their child’s school cared more about the child when they had weeks of absence. All parents maintained that their child’s pain was physical, although they thought that psychological aspects might have influenced the symptoms. The parents stated that they, as well as their children, needed guidance from professionals to understand the complex pain situation.